Data choice in capital gains realisation response studies - a review - Minas, John (Australasian Tax Teachers Association, 2014)
This paper reviews the literature, from the United States, on capital gains realisation response studies. The studies reviewed use the econometric technique of regression analysis to estimate the responsiveness of capital gains realisations to tax rates and this is reported as an elasticity point estimate. The literature review reveals that the use of cross-sectional tax return data for only one tax year is the least preferred of three data types considered. In concluding, the paper considers the implications of the reviewed literature for a forthcoming Australian study on capital gains realisation response.